Analisis Tingkat Pengetahuan Siswa dalam Pembelajaran Permainan Sepakbola Kelas X di SMA Negeri 2 Telukjambe Timur Pada Masa Pandemi Covid-19 - Yusril Abdul Azis; Mury Safei; Siswanto Siswanto (Jurnal Ilmiah Wahana Pendidikan, 2022)
The purpose of this study was to determine students' knowledge of learning football games at SMA Negeri 2 Telukjambe Timur. This type of research is descriptive quantitative. The method used in this research is a survey, the instrument used is multiple choice questions, the sample used in this research is the class X SMA Negeri 2 Telukjambe Timur totaling 135 students. The data analysis used in this study is a descriptive quantitative analysis technique which is described in percentages. In this study, it was successful to show that the understanding of class X students on the understanding of learning football games for the very high category was 1.5%, The purpose of this study was to determine students' knowledge of learning football games at SMA Negeri 2 Telukjambe Timur. This type of research is descriptive quantitative. The method used in this research is a survey, the instrument used is multiple choice questions, the sample used in this research is the class X SMA Negeri 2 Telukjambe Timur totaling 135 students. The data analysis used in this study is a descriptive quantitative analysis technique which is described in percentages. In this study, it was successful to show that the understanding of class X students on the understanding of learning football games for the very high category was 1.5%, the high category was 42.8%, the medium category was 28.9%, the low category was 14.9% and the very low category. by 11.9%.